Word-of-mouth generation and brand communication strategy: Findings from an experimental study explored with PLS-SEM. Issue 3 (10th April 2017) - Andrei, Andreia Gabriela; Zait, Adriana; Vătămănescu, Elena-Mădălina; Pînzaru, Florina
Abstract : Purpose: Emerged from a theoretical contradiction, the purpose of this paper is to investigate whether perceptions and behaviors toward new brands depend on the priority assigned to promote the company's intentions (warmth) vs its abilities (competence). Design/methodology/approach: The research uses a two-level single factor experiment to test the effects of launch communication strategy (warmth-competence vs competence-warmth) on people's perceptions and behavioral intents, and applies partial least squares structural equation modeling to explore the collected data. Findings: Results offer valuable insights into the usage of communication strategy with a view to favor brand perception, referrals, and sales, laying stress on the underlying mechanisms. Research finds that warmth-competence communication strategy has a higher positive influence on brand perception than the reversed strategy. Revealing people's proneness to promote the new companies perceived as warm and competent, results indicate that perception of warmth mediates word-of-mouth propensity. Research limitations/implications: The present study brings novel insights for corporate communication, showing that people's propensity to advocate on behalf of new brands is driven by the perception of company's warmth. Explaining connections between communication strategy, brand perception, and WOM propensity (supportive or denigrating), the current study adds contributions to the previous findings on warmth and competence stereotypes applied to consumer-brand interactions. Practical implications: From a managerial perspective, findings offer practical hints about how to use launch communication to improve brand perception and consumer supportive behaviors. Originality/value: The present study brings novel insights for corporate communication, showing that people's propensity to advocate on behalf of new brands is driven by the perception of company's warmth. Explaining connections between communication strategy, brand perception, and word-of-mouth propensity, the current study adds contributions to the previous findings on warmth and competence stereotypes applied to consumer-brand interactions.